Description of a new species of deep-water king-crab (Crustacea: Decapoda: Anomura) from the southeastern Arabian Sea - Padate, Vinay P.; Cubelio, Sherine Sonia; Takeda, Masatsune (Zootaxa, 2020)
A new species of the deep-water king-crab genus Neolithodes A. Milne-Edwards & Bouvier, 1894 (Anomura: Lithodidae) is described herein from the southeastern Arabian Sea (1064–1338 m depth). Neolithodes indicus sp. nov. shows morphological proximity with three congeneric species, N. brodiei Dawson & Yaldwyn, 1970, N. flindersi Ahyong, 2010a and N. nipponensis Sakai, 1971 in bearing less numerous secondary spines on the carapace, the dactylus of the chelipeds with a convex dorsal margin and dorsoventrally compressed meri of the pereopods 2–4. The new species can be easily distinguished from these congeners in possessing the less densely spinulose carapace and appendages, short rostrum, simple antennal scaphocerite, the absence of large spines on the flexor margins of the pereopods 2–3 meri, and a stouter pereopod 4 propodus.